HCI for peace: from idealism to concrete steps - Hourcade, Juan Pablo; Bullock-Rest, Natasha E.; Friedman, Batya; Nelson, Mark; Shneiderman, Ben; Zaphiris, Panayiotis (My University, 2011)
This panel will contribute diverse perspectives on the use of computer technology to promote peace and prevent armed conflict. These perspectives include: the use of social media to promote democracy and citizen participation, the role of computers in helping people communicate across division lines in zones of conflict, how persuasive technology can promote peace, and how interaction design can play a role in post-conflict reconciliation.
Keywords: Peace; Social media; War; Cyprus; Value sensitive design; Post-conflict reconciliation; Persuasive technology